Program Early Grade Literacy (EGL): Bukti Kolaborasi Efektif antara Pemerintah Indonesia dan UNICEF untuk Pendidikan Papua - Hastira, Muhammad Fajhriyadi; Hastira, Muh. Fichriyadi; Mangiri, Gabriela Karunia (Papua Journal of Diplomacy and International Relations, 2025)
This article aims to discuss the Indonesian government’s efforts to establish international cooperation in the education sector, with a particular focus on United Nations Children’s Fund (UNICEF). It particularly examines how UNICEF can contribute to addressing literacy challenges in Merauke District, Papua—one of the areas where students exhibit low reading and writing skills in the early years of primary education. From an international relations perspective, it highlights how education diplomacy can strengthen local capabilities through global cooperation, exemplified by UNICEF’s Early Grade Literacy Program. Drawing on interviews and program report analysis, this study revealed a significant reduction in non-readers, from almost half to less than a quarter, while the number of students who could read and comprehend texts fluently almost doubled. Creative engagement, like the use of songs, teaching aids, and parent education campaigns, proved the effectiveness of international cooperation at a local scale. These findings not only support the inclusive education targets in the SDGs but also reinforce the strategic role of education diplomacy in addressing disparities in marginalized areas.  KEYWORDS Education; Indonesia; International Cooperation; Papua; UNICEF